Psychological Effects of genocide among the Faili Kurds - Hawzheen Mahmood Azeez; Gian Kamil Hassan (Zanco Journal of Humanity Sciences)
The genocide of the Faili Kurds is a brutal and devastating attack. Successive regimes implemented measures against the Faili in several stages. The persecution which they were subjected to and the trauma they suffered as a result of genocide left far-reaching psychological and social effects in the hearts of their children, youth and elders. Thus, this research aims to identify the most important psychological effects of the genocide, including the effects of post-traumatic stress and psychological distress among the Faili Kurds, and identify the differences in the level of these effects according to the variables: gender, age, educational level, direct and indirect exposure to genocide, their place of settlement after the events of the genocide, and their social status. The sample consisted of (150) Faili Kurds, with (77) males and (73) females. The researchers used the analytical descriptive approach for the purpose of describing, analyzing and interpreting the research variables. and they prepared a scale to measure the effects of post-traumatic stress, and they were adopted (Kessler psychological distress scale). The face validity for the tow scales were verified, as the percentage reached (0.85) for the first scale and (0.90) for the second scale, also extracting the reliability of the two scales were verified, as it reached (0.89) for the first scale, and (0.92) for the second scale. The result has revealed that the respondents have a high level of post-traumatic effects, and a low level of psychological distress. There are no significant differences in post-traumatic effects according to gender, age, but there are significant differences according to the educational level, place of stability, direct or indirect exposure to trauma, and social status, and there are no significant differences in psychological distress according to educational level. But there are significant differences according to gender, direct or indirect exposure to genocide, place of settlement and marital status.